SELF-CONTROL PADA SISWA DENGAN KECANDUAN INTERNET : A LITERATURE REVIEW - Dewi, Widya Novi Angga (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2024)
Background: The increasing use of the internet among adolescents has raised concerns about internet addiction, which can have negative impacts on academics, mental health, and social relationships. This addiction is often associated with low self-control in students. Purpose: This study aims to explore in more depth the characteristics of high school students who are addicted to the internet and what factors influence self-control in high school students with internet addiction. Method: To explore this topic, the method used is a systematic review (Systematic Literature Review/SLR) by collecting and analyzing recent studies from 2020 to 2024 that discuss the factors that influence self-control and its relationship to internet addiction. Results: The results of the literature analysis show that the characteristics of students who experience internet addiction tend to show addictive behavior, which can include excessive use of social media, online games, and other internet activities. Factors that influence self-control include personality traits, especially neuroticism and extroversion. The influence of parenting styles, both permissive and authoritarian, affects children's internet use. Permissive parenting tends to increase addiction, while stricter parenting can reduce online time. Students' self-control is influenced by various factors, including gender, family structure, and social environment. Conclusion: This study suggests that high school students who are addicted to the internet tend to experience addictive behaviors that negatively impact their mental health and academic performance. This addiction is influenced by factors such as personality, parenting style, and social environment.